1993
DOI: 10.3109/00365529309090249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sedation and Supplemental Oxygen during Upper Alimentary Tract Endoscopy

Abstract: The effects of supplemental oxygen therapy on arterial oxygen saturation (SaO2) in unsedated and sedated patients have been studied using pulse oximetry. Hypoxia (minimum SaO2 92% or less) occurred in 41% of unsedated patients breathing room air but in only 11% (p < 0.01) of those receiving supplemental oxygen (41/min) by nasal cannulae. Comparable effects were seen in sedated patients (60% versus 16%, respectively, p < 0.01). Hypoxia during upper alimentary tract endoscopy is common with or without sedation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Although there are no randomised controlled trials comparing air vs. oxygen during ATI, data from bronchoscopy studies demonstrate that there is a significant difference in the incidence and severity of desaturation . In patients receiving sedation in a variety of settings, administration of oxygen has been shown to reduce the incidence of desaturation when compared with air . United Kingdom, European and North American recommendations for sedation all suggest the use of supplemental oxygen .…”
Section: Oxygenationmentioning
confidence: 99%
“…Although there are no randomised controlled trials comparing air vs. oxygen during ATI, data from bronchoscopy studies demonstrate that there is a significant difference in the incidence and severity of desaturation . In patients receiving sedation in a variety of settings, administration of oxygen has been shown to reduce the incidence of desaturation when compared with air . United Kingdom, European and North American recommendations for sedation all suggest the use of supplemental oxygen .…”
Section: Oxygenationmentioning
confidence: 99%
“…During the procedure, standard monitoring procedures should be followed during procedures in the geriatric population. Maintaining a low threshold for beginning supplemental oxygen therapy is important as older patients are at higher risk of oxygen desaturation[ 82 ]. Another serious adverse event is delirium.…”
Section: Practical Considerations For Screeningmentioning
confidence: 99%
“…Supplementary oxygen may increase arterial oxygen saturation during endoscopy4 5 6 7 8 9 but does not decrease the incidence of myocardial ischaemia 4 10 11. Previous studies have suggested tachycardia to be an important pathogenic factor in the development of myocardial ischaemia during endoscopy 1 4.…”
Section: Introductionmentioning
confidence: 99%